1998
DOI: 10.1111/1467-6281.00024
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Standard Costing in the U.K. and U.S.: From Decision Making to Control

Abstract: Decision making and control are two fundamental components of industrial management that are aided by accounting information. This article traces the evolution of standard costing in the U.K. and U.S. and describes how it has served these two purposes over time. At the start of the industrial revolution, standard costing, in the form of past actual costs, aided managers in make-or-buy, pricing, outsourcing and other routine and special decisions. In the late nineteenth century, as the mass production of homoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 29 publications
0
21
0
1
Order By: Relevance
“…Studies conducted using these three perspectives on the emergence of cost management systems, however, have in common an overwhelming reliance on evidence gathered from firms operating in competitive environments, such as those that characterized many Anglo-Saxon industries (e.g., Edwards et al, 1995, p. 2;Fleischman and Tyson, 1998). Therefore, conclusions drawn from such studies are considerably influenced by the conditions of stiff market competition that forged some Anglo-Saxon industries (e.g., the textile and iron sectors: see Edwards and Boyns, 1992;Fleischman et al, 1997;Tyson, 1998).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted using these three perspectives on the emergence of cost management systems, however, have in common an overwhelming reliance on evidence gathered from firms operating in competitive environments, such as those that characterized many Anglo-Saxon industries (e.g., Edwards et al, 1995, p. 2;Fleischman and Tyson, 1998). Therefore, conclusions drawn from such studies are considerably influenced by the conditions of stiff market competition that forged some Anglo-Saxon industries (e.g., the textile and iron sectors: see Edwards and Boyns, 1992;Fleischman et al, 1997;Tyson, 1998).…”
mentioning
confidence: 99%
“…Therefore, conclusions drawn from such studies are considerably influenced by the conditions of stiff market competition that forged some Anglo-Saxon industries (e.g., the textile and iron sectors: see Edwards and Boyns, 1992;Fleischman et al, 1997;Tyson, 1998). Though research on the role of governmental agency in the emergence of cost systems has produced many perceptive insights (e.g., Ezzamel et al, 1990;Tyson, 1993), much is still to be learned about the emergence of cost management practices under monopoly or strict market regulation (e.g., such as those that characterized the economies of both Spain and its overseas colonies).…”
mentioning
confidence: 99%
“…Some academicians affirm that the importance of standard costing and variance analysis for cost control and performance evaluation decreased due to the fierce competitive environment (Kaplan & Johnson, 1987;Monden & Lee, 1993;Ferrara, 1995). Fleischman and Tyson (1998) affirm that the method is inefficient to detect the necessary strategic signals. Other researchers point to the meaningless benefits of the method in respect to highly sophisticated production cycles (Lucas, 1997;Hansen & Mowen, 2002).…”
Section: Scientific Studies In Literaturementioning
confidence: 94%
“…Some academicians suggest that standard costing is no longer suitable in today's highly global and competitive world, and have suggested that firms abandon this method (Kaplan & Johnson, 1987;Monden & Lee, 1993;Ferrara, 1995;Lucas, 1997;Fleischman & Tyson, 1998;Hilton, 2001;Gupta & Gunasekaran, 2004). Drury (2009) stated that the usefulness of standard costing in a modern business environment has been questioned because of the changing cost structure, inconsistency with modern management approaches, over-emphasizes the importance of direct labour, and delay in feedback reporting.…”
Section: Scientific Studies In Literaturementioning
confidence: 99%
“…The data for standard costing were supplied by a Department of Workshop Statistics, formed in 1914; the formation of the department may perhaps be seen as a preparation for the introduction of the standard costing system. An older, 'standard' costing system, with one department for ex ante and one for ex post costing, had been in operation at ASEA from 1911, a relatively early date for standard costing (Fleischman and Tyson 1998), although it has not been possible to find out how this earlier system worked. There is no reference to standard costing in Schmalenbach (1919b) nor AWF (1921a, 1921b, but the latter recommends not only the use of imputed interest and depreciation based on replacement value, but also normal costing and predetermined values for materials and salaries.…”
Section: Is Swedish Cost Accounting Practice An Imitation Of German?mentioning
confidence: 99%